Psychological distress and the COVID-19 pandemic: the role of personality and coping strategies - Sónia Catarina Carvalho Simões; Laura Maria Carreira Marques; Diogo André Fonseca Sequeira de Andrade; Sandra Isabel Ferreira das Neves Henriques; Luís André Abreu Paraíso Ferreira; Helena Maria Amaral do Espírito-Santo (Cadernos de Saúde Pública)
Personality traits and coping strategies significantly predict predisposition to psychopathology. This study aimed to examine the predictive role of coping strategies in psychological distress during the COVID-19 pandemic in a sample of Portuguese individuals, considering personality and sociodemographic variables. Data were collected using Google Forms from 2402 individuals (86.8% women; mean age ± SD = 36.80 ± 11.80) between March and June 2020, found primarily through Facebook. The evaluation instruments included the Brief Symptom Inventory (BSI), NEO Five-Factor Inventory, and Brief-COPE. Younger adults, females, single individuals, and those with lower education experienced higher distress. Neuroticism was strongly associated with all dimensions of psychological distress and the overall BSI. Maladaptive coping strategies (self-distraction, denial, self-blame, behavioral disengagement) were positively correlated with distress, whereas agreeableness and positive reframing were negatively correlated. Regression analysis showed that gender, age, education, and psychiatric diagnosis predicted 12% of distress; adding neuroticism increased prediction to 34% and coping strategies to 37%, with self-blame among coping strategies being the strongest predictor. Personality traits and coping strategies were significant predictors of psychological distress during the COVID-19 pandemic. These findings emphasize the need for interventions that target neuroticism and maladaptive coping strategies to improve mental health outcomes during public crises.